The Future of Problemy Ekorozwoju/ Problems of Sustainable Development Journal - Pawłowski, Artur (Problemy Ekorozwoju, 2023)
In 2023 Problemy Ekorozwoju/ Problems of Sustainable Development turned 18, entering adulthood one could say. The journal debuted on January 1, 2006 as a philosophical journal published only in Polish. From 2008 we begun to publish papers also in English and soon decided to publish only in English. The scope of the journal was expanded and we begun to be multidisciplinary, publishing papers from the humanities, economics and technical sciences (especially environmental engineering).We have always, however, been devoted to sustainable development problematics. Our wider approach offers a chance for Polish scientists to present their research in an international journal (also from the field of humanities, where there are fewer possibilities for international presentations) to foreign scholars and vice versa. Since there are no fees, the journal also is more accessible for scientists from poorer countries. So far we have published 36 numbers (18 issues) with almost 700 scientific papers. From 2010 the journal has been fully indexed in the Web of Science and Scopus. The current IF is 1.1 (in the previous year it was 0.864). Other metrics include: CiteScore (Scopus): 1.9, highest percentile: 57%, Index Copernicus Value ICV: 148.59 and SJR Scimago Journal & Country Rank h-Index: 21. Over the last few years one could observe improvement in all of our international parameters. We have always been an Open Access journal. In recent years we introduced DOI numbers, Open Access Statement and Copyright Rights, Publication Ethics and Malpractice Statement. Soon we will also be visible in the Journal Checker Tool. From this number we are introducing Open Journal System (OJS). Currently the journal has the patronage of the European Academy of Science and Arts (Salzburg, Austria). The publisher is and has always been the Lublin University of Technology (Lublin, Poland).